Pregnancy outcomes in women complicated by thalassemia syndrome at Maharaj Nakorn Chiang Mai Hospital - Kuntharee Traisrisilp (2018)
Objective: To determine the maternal and fetal outcomes of women complicated with thalassemia syndrome. Study design: Retrospective descriptive study. Materials and methods: The database of Maternal-Fetal Medicine unit and medical records, between January 2001 and April 2008, were reviewed to search for pregnant women complicated with thalassemia syndrome and medical records were reviewed for patient's baseline characteristics and pregnancy outcomes. The inclusion criteria consisted of (1) pregnant women diagnosed for thalassemia syndrome by hematologist either during or before pregnancy based on hemoglobin typing, (2) attending the antenatal care clinic and delivery at Maharaj Nakorn Chiang Mai hospital, and (3) available data of pregnancy outcomes. Results: During the study period, 80 pregnant women with thalassemia syndrome were recruited, including 52 (65%) cases of HbH disease, 23 (28.8%) cases of beta-thalassemia/HbE disease, 2 cases of AE Bart's disease, 2 cases of EF Bart's disease and 1 case of beta-thalassemia major. Excluding 2 twin pregnancies and 1 case with beta-thalassemia major, 77 were available for analysis of the outcomes. The mean gestational age (±SD) at delivery was 37.40 (±2.6) weeks, range 27-42 weeks. Twenty-five (32.5%) had delivery by cesarean section and the remainder had successful vaginal delivery. Fetal growth restriction was found in 21 cases (27.3%), 16 (20.8%) had preterm births and the rate of low birth weight (<2,500 g) was 44.1%. Regard to the type of thalassemia, baseline hemoglobin levels and mean birth weight of women with beta-thal/Hb E was significantly lower than the levels of those with Hb H disease. Conclusion: This series indicates that, in spite of an attempt to keep hemoglobin levels above 7.0 g/dl, pregnancy with thalassemia is likely to be associated with an increased rate of fetal growth restriction, preterm birth and low birth weight. © 2008 Springer-Verlag.